Popular peers and firstborn siblings are better off (Sociologisk Forskning, 2017)
‘The apple doesn’t fall far from the tree’ is an idiom that ultimately is reflected in the reproduction of inequality patterns across generations. Representatives of the child’s own generation, such as siblings and peers, may however play a key role by either reinforcing or counteracting this reproduction. Based on a Stockholm cohort now approaching retirement, we explore whether the inheritance of parents’ misfortunes, here reflected through poverty, varies in strength depending on the cohort members’ position in the sibship or peer group.